Physical activity promotion in community pharmacies: pharmacists’ attitudes and behaviours - Viegas, Rúben (2021)
Background: Health systems and their professionals play a key role in the promotion and maintenance of behaviours contributing to increased physical activity levels. Pharmacists are well placed within communities, making them an accessible source to provide brief advice to people on how to be more physically active. Objective: This study aimed to characterize physical activity promotion actions taking place in the Portuguese community pharmacies, as well as the major facilitators and barriers faced by pharmacists in their daily practice. Methods: A cross-sectional study based on an online questionnaire targeting community pharmacists was developed based on COM-B model and the Theoretical Domains Framework (TDF) and distributed by email to 94% of the Portuguese pharmacies. Results: In total, 396 complete responses from community pharmacists were obtained. Three out of four participants reported to promote physical activity in their daily routine, of which 87.7% reported doing it in only a few attendances. The majority (92.3%) mentioned to provide information orally, with walking being the activity most promoted (99.4%). More active and younger pharmacists were more likely to promote physical activity. Nearly all pharmacists (98.7%) believed it was important or very important to practice regular physical activity for the health, but only 41.4% of the respondents were able to correctly identify the WHO general recommendations for physical activity. The lack of coordination with other healthcare professionals (M=3.35; SD=1.11), lack of interest by customers (M=3.25; SD=1.09) and lack of time (M=3.06; SD=1.10) were the main barriers to physical activity promotion, all scoring above the scale mid-point (i.e., 3). Conclusions: Physical activity promotion in the Portuguese community pharmacies is still not present as daily activity. Younger pharmacists seem to be a generation that better understand this need and could easily integrate this practice in their daily routine. Possibilities for including pharmacies and pharmacists as promoters of physical activity in the primary health care sector in the future are discussed in the light of these findings.